Probable Three-Species In Vivo Transfer of blaNDM-1 in a Single Patient in Greece: Occurrence of NDM-1-Producing Klebsiella pneumoniae, Proteus mirabilis, and Morganella morganii - Georgios Meletis; Andigoni Malousi; Areti Tychala; Angeliki Kassomenaki; Nikoletta Vlachodimou; Paraskevi Mantzana; Simeon Metallidis; Lemonia Skoura; Efthymia Protonotariou (MDPI AG, 2023)
NDM carbapenemase-encoding genes disseminate commonly among Enterobacterales through transferable plasmids carrying additional resistance determinants. Apart from the intra-species dissemination, the inter-species exchange of plasmids seems to play an additional important role in the spread of blaNDM. We here present the genetics related to the isolation of three species (Klebsiella pneumoniae, Proteus mirabilis, and Morganella morganii) harboring the blaNDM-1 gene from a single patient in Greece. Bacterial identification and antimicrobial susceptibility testing were performed using the Vitek2. Whole genome sequencing and bioinformatic tools were used to identify resistance genes and plasmids. BlaNDM-1 harboring plasmids were found in all three isolates. Moreover, the plasmid constructs of the respective incomplete or circular contigs showed that the blaNDM-1 and its neighboring genes form a cluster that was found in all isolates. Our microbiological findings, together with the patient's history, suggest the in vivo transfer of the blaNDM-1-containing cluster through three different species in a single patient.